Ammonia sensor based on perovskite quantum dots and ammonia quantitative detection method

By using perovskite quantum dot film as an ammonia sensor for gas sensitive elements, the problems of high operating temperature and poor selectivity of gas sensors in the prior art are solved, and specific ammonia detection with high sensitivity and room temperature response are achieved.

CN113155785BActive Publication Date: 2025-02-11JILIN UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202010015071.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-01-07
Publication Date
2025-02-11
Estimated Expiration
2040-01-07

AI Technical Summary

Technical Problem

Existing gas sensors have high operating temperature and poor selectivity, making it difficult to achieve specific ammonia detection with high sensitivity and room temperature response.

Method used

The ammonia gas sensor based on perovskite quantum dots is used, and the perovskite quantum dot film is used as a gas-sensitive element, and combined with a fluorescent gas-sensitive sensing system, the intensity changes of the fluorescent signal are captured for ammonia concentration detection.

Benefits of technology

It realizes accurate measurement of ammonia in the range of 25ppm-350ppm, has fast response recovery speed, good selectivity, is suitable for room temperature environments, and is cheap.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113155785B_ABST
    Figure CN113155785B_ABST
Patent Text Reader

Abstract

The present invention discloses an ammonia sensor based on perovskite quantum dots and a quantitative ammonia detection method. The gas-sensitive element of the ammonia sensor includes a perovskite quantum dot film, and the perovskite quantum dots are perovskite quantum dots with defects on the surface. The ammonia sensor in the present invention has a simple structure and can realize dynamic monitoring of ammonia content. The ammonia detection method in the present invention can realize accurate measurement of low-concentration ammonia by using the change value of fluorescence intensity, and the method does not require an excessively high operating temperature, and can realize quantitative detection of ammonia concentration at room temperature. It has the characteristics of simple measurement method, low component cost, fast response recovery speed, good detection selectivity, and good detection performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of gas sensors, and in particular relates to an ammonia sensor based on perovskite quantum dots and a method for quantitatively detecting ammonia. Background Art

[0002] Ammonia is a colorless gas with a strong pungent odor and is easily soluble in water. Ammonia is a carcinogenic and teratogenic substance that can cause certain damage to the human eyes, respiratory system, nervous system and internal organs. When exposed to an ammonia environment, the skin tissue that comes into contact with ammonia will be corroded and irritated by ammonia. Ammonia will also absorb moisture from the surface of the skin, causing protein denaturation on the surface of the skin and destroying the tissue structure. In addition, ammonia can also cause strong irritation and corrosion to the eyes and respiratory system. Ammonia is easily adsorbed on the conjunctiva of the eyes and the mucosa of the respiratory tract, causing conjunctivitis and respiratory inflammation. Due to the destructive effect of ammonia on the mucosa of the respiratory tract, pathogenic microorganisms are more likely to invade the human body. In industry, ammonia can be used in the industrial production of raw materials such as fertilizers and refrigeration systems. If an ammonia leak occurs, it will cause the factory to close and damage the environment.

[0003] Gas sensors use sensitive materials to directly adsorb target gases, causing changes in the electrical or optical properties of the materials, and then output electrical or optical signals to detect gas concentrations based on changes in these signals. Most sensors can be divided into sensors based on electronic signals and sensors based on optical signals, in which gas sensing responses can be recorded by changes in electrical and optical properties, respectively. In terms of sensors based on electronic signals, most are metal oxide semiconductor gas sensors, such as TiO2, SiO2 or ZnO, which have poor temperature dependence and often require operating temperatures above 300°C, which brings difficulties to practical applications. Optical sensors can be divided into two types: one is to detect changes in the absorption of light by the target gas as a detection signal, which shows good sensitivity and selectivity, but the high requirements for equipment further limit their application as portable micro sensors; the other is a sensor based on the reaction between the sensor sensitive layer and the target gas to trigger an optical signal, such as a sensor with fluorescence or color changes as a detection signal.

[0004] Since ammonia is an alkaline gas, at a certain concentration, it can change the color of the test paper, thereby analyzing whether there is ammonia in the atmosphere. However, this test requires that the ammonia concentration is high and the color change of the test paper is sensitive, otherwise a large error will occur. In addition, most of the ammonia sensors based on fluorescence intensity changes are fluorescence attenuation sensors. Since the sensor has a relatively complex working environment, other gases will also affect the sensitive layer and cause fluorescence attenuation, thereby affecting the selectivity and sensitivity of the sensor.

[0005] Therefore, it is necessary to develop a specific fluorescence-enhanced ammonia sensor with high sensitivity and suitable for room temperature response. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the defects of high operating temperature and poor selectivity of gas sensors in the prior art, and to provide an ammonia sensor based on perovskite quantum dots and ammonia quantitative detection method. The ammonia sensor in the present invention has a simple structure, selects a perovskite quantum dot film as a gas-sensitive element, and then uses a fluorescent gas-sensitive sensor system to capture the intensity change of the fluorescence signal of the element to detect the ammonia concentration. The ammonia sensor can realize dynamic monitoring of ammonia content. The ammonia detection method in the present invention can realize accurate measurement of low-concentration ammonia (for example, in the range of 25ppm-350ppm) by using the change value of fluorescence intensity, and the method does not require an excessively high operating temperature, and can realize the measurement of ammonia concentration at room temperature. It has the characteristics of simple measurement method, low component cost, fast response recovery speed, and good detection selectivity, and has good detection performance.

[0007] The ammonia sensor of the present invention can accurately measure the ammonia concentration. The core is that it uses perovskite quantum dots as the gas-sensitive element of the sensor. At room temperature, perovskite quantum dots have a good response to ammonia in the range of 25ppm-350ppm, and there is a good linear relationship between the ammonia concentration and the response value. The inventors have discovered the underlying reason through extensive research: perovskite quantum dots are an ionic crystal, and the ligands bound to the surface of the quantum dots are highly dynamic, and their surface diffusion coefficient is higher than that of traditional quantum dots with strong covalent properties, which makes them easy to fall off the surface during the purification process. During the formation of the synthesized perovskite quantum dots, the unpaired B 2+ (Pb 2+ Sn 2+ ,Ge 2+ One or more of the above mentioned surface trap states lead to obvious defects in perovskite quantum dots. A large number of studies have shown that surface defects may directly lead to a sharp decrease in the photoluminescence quantum yield (PLQY) and multi-component excited state photoluminescence (PL) of perovskite quantum dots. After much creative work, the inventors found that ammonia with lone pairs of electrons can bind to unsaturated B on the surface of perovskite. 2+ (Pb 2+ Sn 2+ ,Ge 2+ The fluorescence intensity of perovskite quantum dots can be increased, and there is a good response between the two, which can accurately quantify the concentration of ammonia.

[0008] The present invention provides an ammonia sensor based on perovskite quantum dots, comprising:

[0009] A gas sensor, used to sense the concentration of ammonia and convert it into fluorescence intensity, wherein the gas sensor includes a perovskite quantum dot film, wherein the perovskite quantum dots in the perovskite quantum dot film are perovskite quantum dots with defects on the surface;

[0010] An excitation light source, used for irradiating the gas-sensitive element to generate a fluorescent signal;

[0011] The fluorescence receiving element is used to receive the fluorescence signal generated by the gas-sensitive element and record the corresponding fluorescence intensity.

[0012] In the present invention, the perovskite quantum dots generally refer to nano-scale perovskite crystals.

[0013] In the present invention, the perovskite quantum dots with defects on the surface generally refer to perovskite quantum dots with unbonded atoms or broken bond atoms on the surface, such as iodine vacancy defects, lead vacancy defects, iodine-for-lead vacancy defects or lead-for-iodine vacancy defects in CH3NH3PbI3.

[0014] In the present invention, the surface defects of the perovskite quantum dots can be judged by the photoluminescence quantum yield of the perovskite quantum dots. Generally speaking, perovskite quantum dots with a luminescence yield of <100% (eg, 0%-90%) can be considered as perovskite quantum dots with surface defects.

[0015] In the present invention, the structural formula of the perovskite in the perovskite quantum dot may be ABX3, wherein A may be a methylamine cation CH3NH3 + 、Formamidinium cation HC(NH2)2 + , Cesium ion Cs + and rubidium ions Rb + One or more of, preferably cesium ion Cs + ; The B may be a lead ion Pb 2+ 、Sn 2+ and germanium ion Ge 2+ One or more of, preferably lead ion Pb 2+ ; X can be an iodide ion I - 、Br - and chloride ion Cl - One or more of, preferably bromide ion Br - .

[0016] Among them, preferably, the perovskite quantum dots are CsPbBr3 quantum dots.

[0017] The perovskite quantum dots can be prepared by hot injection synthesis, vapor deposition, supersaturated recrystallization, inversion crystallization or microwave method. Generally speaking, the perovskite quantum dots are stored in the form of a precursor solution.

[0018] The hot injection synthesis method can be carried out according to the following steps: in a solvent, the A-ligand and BX are mixed and reacted to obtain the precursor solution of the perovskite quantum dots; wherein the A, the B and the X are the same as described above.

[0019] The solvent may be a conventional solvent in the art, such as octadecene.

[0020] The A in the A-ligand is preferably a cesium ion Cs + .

[0021] The ligand in the A-ligand may be a conventional ligand in the art, such as oleic acid or oleylamine.

[0022] The A-ligand can be prepared by the following method: a compound containing A and a ligand (such as oleic acid) are mixed, dried at 110-130° C. (such as 120° C.) for 0.5-1.5 h (such as 1 h), and reacted at 60-200° C. (such as 160° C.) under a nitrogen atmosphere to obtain the compound containing A. The compound containing A can be Cs2CO3.

[0023] The A-ligand may be mixed with the BX at a concentration of 0.01 mol / mL.

[0024] The B is preferably lead ion Pb 2+ .

[0025] The X is preferably a bromide ion Br - .

[0026] Preferably, the hot injection synthesis method is carried out according to the following steps: in a solvent, the ligand solution in the A-ligand is first mixed with BX, and then mixed with the A-ligand for a second time. The conditions of the first mixing can be: vacuuming at 120° C. for 30 minutes and heating to 180° C. under nitrogen flow for mixing.

[0027] After the A-ligand and the BX are mixed, the reaction mixture should generally be cooled using an ice-water bath within 5 seconds.

[0028] In the hot injection synthesis method, after the reaction is completed, post-treatment can be performed according to conventional means in the art, such as centrifugation, washing and purification. The centrifugation condition can be centrifugation at 4000-8000 rpm for 10 minutes. The washing solvent can be methyl acetate. The volume ratio of the precursor solution of the perovskite quantum dots to the washing solvent can be 1: (1-1.5), such as 1: 1, 1: 1.2 or 1: 1.5. The number of centrifugation, washing and purification treatments can be 1 or 2 times.

[0029] After the washing and purification treatment, a dispersion treatment should generally be performed. The dispersion solvent may be one or more of benzene, toluene, chlorobenzene, xylene, n-heptane, n-hexane and n-octane, such as toluene or n-hexane.

[0030] In the present invention, preferably, the perovskite quantum dots are in a cubic phase and have a size of 4-15 nm, such as 10 nm.

[0031] In the present invention, the perovskite quantum dot film can be attached to the surface of the fluorescence receiving element or the surface of the carrier device.

[0032] The object carrier may be a conventional object carrier in the art, such as quartz glass or a flexible substrate. The flexible substrate may be a polyethylene flexible substrate, a PET substrate, a PMMA substrate or paper.

[0033] The quartz glass or the flexible substrate may be pretreated by conventional means in the art, such as wiping with acetone and then ultrasonically cleaning. The ultrasonic cleaning may be performed by sequentially placing in isopropanol-acetone-water-acetone-isopropanol for ultrasonication. The ultrasonication time may be 15 minutes. After the ultrasonication, a drying treatment may be performed, such as drying in a 70°C oven for standby use.

[0034] When the flexible substrate is paper, it is generally not subjected to the above-mentioned pretreatment.

[0035] When the perovskite quantum dot film is attached to the surface of the carrier device to form the gas sensor, the gas sensor can be placed between the excitation light source and the fluorescence receiving element. For example, the excitation light source emits a laser to irradiate the gas sensor, the gas sensor emits fluorescence, and the fluorescence receiving element can receive the fluorescence in the direction opposite to the excitation light source.

[0036] When the perovskite quantum dot film is attached to the surface of the fluorescence receiving element, the fluorescence receiving element can receive the light emitted by the excitation light source. For example, the excitation light source and the fluorescence receiving element are arranged opposite to each other.

[0037] The perovskite quantum dot film can be prepared according to the following steps: coating a precursor solution of the perovskite quantum dots on the surface of the fluorescent receiving element or the surface of the carrier device.

[0038] The coating method may be a conventional method in the art, such as spin coating, blade coating, drop coating or slot extrusion coating.

[0039] In the spin coating method, the spin coating conditions may be firstly 1000 rpm for 10 seconds and then 2000 rpm for 20 seconds.

[0040] After the spin coating, the precursor solution can be post-processed by conventional means in the art, such as being placed in a vacuum oven for suction to evaporate the solvent in the precursor solution. After the suction is completed, the precursor solution can be placed in a nitrogen atmosphere for protection and standby.

[0041] In the present invention, the excitation light source may be a conventional excitation light source in the art, such as an LED lamp.

[0042] In the present invention, the excitation wavelength of the excitation light source can be adjusted according to the type of quantum dots. For example, when the perovskite quantum dots are CsPbBr3 quantum dots, the wavelength of the excitation light source can be 365 nm.

[0043] In the present invention, the fluorescence receiving element may be a conventional fluorescence receiving element in the art, such as a diode, and also such as a silicon diode.

[0044] Preferably, the silicon diode has a built-in filter, which can filter out the excitation light while receiving the quantum dot fluorescence signal, thereby improving the sensitivity of the device. In addition, the silicon diode with a filter can collect fluorescence signals of multiple wavelengths in real time, thereby simplifying the sensor structure and reducing costs.

[0045] In the present invention, the gas sensor, the excitation light source and the fluorescence receiving element can be placed in a housing.

[0046] The excitation light source and the fluorescence receiving element may be connected to the housing via a fixing device, which may be a screw.

[0047] Preferably, a socket structure is provided between the excitation light source and the fluorescence receiving element, and the socket structure is fixed inside the housing. The socket structure can be used to place the gas sensor, for example, the perovskite quantum dot film is attached to the aforementioned carrier to form the gas sensor.

[0048] The shell may be a black hollow structure, such as a black rectangular hollow structure. The shell may be made of polymer material.

[0049] When the shell is a black hollow structure, the shell can avoid interference from external light, ensure that the internal state of the shell is not affected by external light, and ensure the stability of the optical signal information.

[0050] Preferably, the shell is also provided with an air inlet and an air outlet, which can be used for introducing and releasing airflow.

[0051] The air inlet and the air outlet may be respectively arranged on different sides of the shell, or may be arranged on the same side of the shell. Preferably, the air inlet and the air outlet are arranged opposite to each other.

[0052] When the housing is provided with an air inlet and an air outlet arranged opposite to each other, preferably, the air flow direction of the air inlet and the air outlet is arranged in parallel with the gas sensor. For example, when the housing is also provided with a socket structure, and the gas sensor is placed in the socket structure, the air inlet and the air outlet are arranged above the socket structure. This structure is conducive to the gas to fully contact and react with the quantum dots when passing through the detection device, and produce corresponding fluorescence changes.

[0053] The air inlet and / or the air outlet may be provided with a desiccant or a molecular sieve to remove water vapor and / or other gases except ammonia.

[0054] Preferably, the air inlet and / or the air outlet can be connected to an air pump.

[0055] When the air inlet and the air outlet are provided on the shell, the sensor can realize dynamic detection of ammonia concentration.

[0056] When the shell is not provided with an air inlet and an air outlet, or when the air inlet and the air outlet are blocked (for example, by setting a rubber stopper), a needle tube injection can be used for sampling, and the sensor can realize static detection of ammonia concentration.

[0057] In the present invention, the ammonia sensor generally further comprises a signal analysis system, which is connected to the fluorescence receiving element. The signal analysis system can receive the fluorescence signal from the fluorescence receiving element, analyze it and output an electrical signal.

[0058] Wherein, the signal analysis system can be a computer, an integrated circuit or a chip.

[0059] In the present invention, preferably, the ammonia sensor comprises:

[0060] A perovskite quantum dot film, wherein the perovskite quantum dots in the perovskite quantum dot film are perovskite quantum dots with defects on the surface;

[0061] An LED lamp, used to excite the perovskite quantum dots to generate fluorescent signals;

[0062] A silicon diode, wherein the silicon diode has a built-in filter for receiving the fluorescence signal of the perovskite quantum dots and filtering out the excitation light;

[0063] A quantum dot carrier device, the quantum dot carrier device is placed between the LED lamp and the silicon diode;

[0064] a signal analysis system, used to analyze and output the change of the fluorescent signal received by the silicon diode;

[0065] The perovskite quantum dot film is directly coated on the surface of the silicon diode or on the surface of the carrier device;

[0066] The LED lamp, the silicon diode and the quantum dot carrier are placed in a shell, the shell is a black rectangular hollow structure, and the LED lamp and the silicon diode are connected to the shell through a fixing device;

[0067] When the perovskite quantum dot film is coated on the surface of the carrier, a socket structure is arranged on the shell, and the quantum dot carrier is connected to the shell through the socket structure. The shell is provided with an air inlet and an air outlet which are arranged opposite to each other, and the air inlet and the air outlet are arranged above the socket structure.

[0068] In the present invention, the ammonia sensor can perform detection within a temperature range of -50°C to 130°C, such as -40°C, 50°C or 70°C.

[0069] The present invention also provides a method for quantitative detection of ammonia, which comprises the following steps:

[0070] (1) Under the irradiation of excitation light, a standard curve of ammonia concentration-fluorescence intensity is constructed using a gas sensor (F-F0) / F0-[Q], wherein: F is the fluorescence intensity of the gas sensor when it contacts ammonia, F0 is the fluorescence intensity of the gas sensor before contacting ammonia, and [Q] is the ammonia concentration;

[0071] The gas sensor is as described above;

[0072] (2) Under the irradiation of the excitation light, the fluorescence intensity of the gas sensor before contacting the gas to be measured is detected, which is recorded as F0', and the fluorescence intensity of the gas sensor after contacting the gas to be measured is detected, which is recorded as F';

[0073] The concentration of ammonia in the gas to be tested can be calculated according to the standard curve in step (1).

[0074] In step (1), the excitation light is generated by an excitation light source, which is as described above.

[0075] In step (1), the standard curve can be obtained by the following method: after calibrating the ammonia concentration in the environment, under the irradiation of excitation light, the fluorescence intensity at each ammonia concentration is detected, and a standard curve of (F-F0) / F0-[Q] is drawn.

[0076] In step (1), the (F-F0) / F0 and the ammonia concentration show a good linear relationship between 100ppm and 900ppm, wherein: when the ammonia concentration is 25-50ppm, the standard curve can be (F-F0 / F0)=0.00219+0.00166[Q](R 2 >0.98); when the ammonia concentration is 50-350 ppm, the standard curve can be (F-F0) / F0=0.07197+3.83038×10 -4 [Q](R 2 >0.98).

[0077] In the present invention, the quantitative detection of ammonia can be performed in the ammonia sensor based on perovskite quantum dots as described above.

[0078] The present invention also provides an application of perovskite quantum dots as gas sensitive elements in ammonia detection.

[0079] The ammonia detection environment may be a conventional detection environment in the art, such as in food, in a sealed environment or in other open environments.

[0080] The present invention also provides a perovskite quantum dot, the surface of the perovskite quantum dot includes a passivation layer, and the passivation layer is a structure formed by passivating the surface defects of the perovskite quantum dot by ammonia; the perovskite quantum dot is as described above.

[0081] Among them, the surface defects of perovskite quantum dots generally come from lattice defects or coordinated dangling bonds on the surface of quantum dots, such as vacancy defects caused by missing cationic components (Cs vacancies, amine vacancies, etc.), unpaired B 2+ (Pb 2+ Sn 2+ ,Ge 2+ Defects caused by one or more of the above), defects caused by surface metal lead, defects caused by the interaction between the solvent and the surface, defects caused by the shedding of surface ligands, defects caused by surface decomposition caused by water and oxygen, etc.

[0082] The passivation generally refers to the elimination of surface defects or dangling bonds of quantum dots.

[0083] In the present invention, the room temperature refers to 25°C±5°C.

[0084] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0085] The reagents and raw materials used in the present invention are commercially available.

[0086] The positive and progressive effects of the present invention are:

[0087] (1) The ammonia gas sensor of the present invention utilizes the excellent luminescence properties of perovskite quantum dots of perovskite materials to monitor the changes in the fluorescence intensity of the gas-sensitive element. It has a good response to ammonia in the range of 25ppm-350ppm, with a detection limit as low as 8.85ppm, and a good linear law between the ammonia concentration and the response value.

[0088] (2) The ammonia sensor of the present invention has the characteristics of specific fluorescence enhancement for ammonia, fast response recovery speed, and good selectivity for ammonia. Moreover, it can be applied to room temperature monitoring environment, overcoming the disadvantage of ultra-high operating temperature of other detectors.

[0089] (3) The ammonia sensor of the present invention has a simple structure, a convenient preparation process, low cost, excellent performance, and good detection performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0090] Figure 1 This is a transmission electron microscope image of the perovskite quantum dots prepared in Example 1.

[0091] Figure 2 for Figure 1 A partial enlarged schematic diagram (magnification is 1 million times).

[0092] Figure 3 Schematic diagram of the ammonia sensor prepared in Example 1, in which the arrows indicate the direction of ammonia gas flow.

[0093] Figure 4 The response value of the ammonia sensor prepared in Example 1 at room temperature 25° C. and the ammonia concentration are plotted, wherein the response value represents the ratio of the relative fluorescence intensity change of the device in ammonia to the original fluorescence intensity.

[0094] Figure 5 The response value of the ammonia sensor prepared in Example 1 at room temperature 25°C and the recovery response curve of ammonia concentration, wherein the response value represents the ratio of the relative fluorescence intensity change of the device in ammonia to the original fluorescence intensity.

[0095] Figure 6 This is the response recovery curve of the ammonia sensor prepared in Example 1 at room temperature of 25° C. and an ammonia concentration of 35 ppm.

[0096] Figure 7 This is the response recovery curve of the ammonia sensor prepared in Example 2 at room temperature of 25° C. and an ammonia concentration of 50 ppm.

[0097] Figure 8 This is the response recovery curve of the ammonia sensor prepared in Example 3 at room temperature 25° C. and an ammonia concentration of 100 ppm.

[0098] Fig. 9 Schematic diagram of the detection object selection characteristics of the ammonia sensor prepared in Example 1 under the conditions of an operating temperature of 25° C. and a gas concentration of 100 ppm.

[0099] Fig.10 Schematic diagram of the combination model of the perovskite quantum dots prepared in Example 1 and ammonia.

[0100] Fig.11 This is the XPS spectrum of the perovskite quantum dots prepared in Example 1 before ammonia treatment.

[0101] Fig.12 This is the XPS spectrum of the perovskite quantum dots prepared in Example 1 after ammonia treatment.

[0102] Fig.13 This is a graph showing the change in the response value of the ammonia sensor when the operating temperature of the perovskite quantum dot ammonia gas sensor in Example 1 is between -40°C and 70°C.

[0103] The accompanying drawings are as follows:

[0104] 1. Air outlet;

[0105] 2 LED bulbs;

[0106] 3 Air inlet;

[0107] 4. Gas sensor;

[0108] 5. Jack structure;

[0109] 6' Silicon diode;

[0110] 6. Filters;

[0111] 7 Silicon diode body;

[0112] 8 housing;

[0113] 9. Signal analysis system;

[0114] 10 Ammonia sensor. DETAILED DESCRIPTION

[0115] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0116] Example 1

[0117] (1) First, cut the quartz glass into 1 cm × 1 cm pieces using a glass cutter, wipe the surface stains with an acetone cotton ball, and then place the quartz substrate in isopropanol-acetone-water-acetone-isopropanol ultrasonic treatment for 15 min each, and dry it in a 70°C oven for later use.

[0118] (2) Perovskite quantum dots were synthesized by hot injection. Cs2CO3 (0.814 g) was added to a 100 mL three-necked flask together with octadecene (ODE) (30 mL) and oleic acid (OA) (2.5 mL), dried at 120 °C for 1 h, and then heated to 160 °C under N2 until all Cs2CO3 reacted with OA to obtain cesium oleate solution. The cesium oleate solution was kept at 160 °C before injection to avoid solidification. 24.0 mL ODE, 10 mL OA and PbBr2 (1.38 g) were placed in a 250 mL flask, vacuumed at 120 °C for 30 min and heated to 180 °C under nitrogen flow. 8 mL of cesium oleate solution (0.08 mol in ODE) was quickly injected. Within 5 s, the reaction mixture was cooled using an ice-water bath. The crude solution was directly centrifuged at 8000 rpm for 10 min, and the precipitate was collected and dispersed in toluene. The final quantum dots need to be purified by centrifugation again. Then the obtained quantum dot precursor solution and methyl acetate are mixed in a volume ratio of 1:1 (quantum dots: methyl acetate), shaken and centrifuged in a centrifuge at 4000 rpm for ten minutes, the precipitate is dispersed with toluene and stored at 8°C for later use.

[0119] (3) Preparation of perovskite quantum dot film. The precursor solution needs to be purified with methyl acetate. The purification step is to purify the perovskite quantum dot precursor solution to be purified and methyl acetate twice at a volume ratio of 1:1.5. The specific purification step is: mix the perovskite quantum dot solution and methyl acetate at a volume ratio of 1:1.5, shake and centrifuge at 4000 rpm for ten minutes, pour off the upper clear liquid, and disperse the lower solid with toluene.

[0120] Then, a fixed amount of the purified precursor solution (20 μL) was spin-coated onto a quartz glass plate to obtain a uniform precursor coating. Spin coating parameters: 1000 rpm for 10 s, 2000 rpm for 20 s. The quartz plate with the precursor coating was then placed in a vacuum oven to accelerate the evaporation of toluene under vacuum suction. The plate was placed in a nitrogen atmosphere for protection and then stored for later use. Figure 1 , Figure 2 As shown, the prepared perovskite quantum dots are regular cubic phases with a particle size of about 10 nm.

[0121] (4) Using the perovskite quantum dot film in step (3) to prepare an ammonia gas sensor 10, such as Figure 3The device includes an LED bulb 2 for exciting quantum dot fluorescence; a silicon diode 6' for receiving quantum dot fluorescence signals, wherein the silicon diode 6' includes a filter 6 and a silicon diode main body 7; a quartz plate 4 coated with a perovskite quantum dot film; a housing 8, which is a black rectangular hollow structure, and the internal state of the housing is not affected by external light; an air inlet 3 and an air outlet 1, which are respectively disposed on both sides of the housing; a socket 5 for placing a quartz plate with a perovskite quantum dot film attached is fixed inside the housing; and a signal analysis system 9.

[0122] The working principle of the above-mentioned ammonia gas sensor is: before detection, a quartz plate coated with a perovskite quantum dot sensitive layer is inserted into 5 (or directly coated on the surface of the silicon diode 7 body); during detection, the LED excitation light is turned on, and the excitation light is irradiated on the quantum dots to produce fluorescence. The detection gas enters through the air inlet 3, and the molecular sieve arranged at the air inlet 3 adsorbs interfering gases and moisture. The gas to be detected contacts the surface of the quantum dot film, causing the fluorescence intensity of the quantum dots to change. The changed fluorescence intensity is collected via the silicon diode 6' and the signal is output via the signal processing system 9 (which can be a computer, an integrated circuit or a chip).

[0123] Example 2

[0124] (1) First, cut the quartz glass into 1 cm × 1 cm pieces using a glass cutter, wipe the surface stains with an acetone cotton ball, and then place the quartz substrate in isopropanol-acetone-water-acetone-isopropanol ultrasonic treatment for 15 min each, and dry it in a 70°C oven for later use.

[0125] (2) Perovskite quantum dots were synthesized by hot injection. Cs2CO3 (0.814 g) was added to a 100 mL three-necked flask together with octadecene (ODE) (30 mL) and oleic acid (OA) (2.5 mL), dried at 120 °C for 1 h, and then heated to 160 °C under N2 until all Cs2CO3 reacted with OA to obtain cesium oleate solution. The cesium oleate solution was kept at 160 °C before injection to avoid solidification. 24.0 mL ODE, 10 mL OA and PbBr2 (1.38 g) were placed in a 250 mL flask, vacuumed at 120 °C for 30 min and heated to 180 °C under nitrogen flow. 8 mL of cesium oleate solution (0.08 mol in ODE) was quickly injected. Within 5 s, the reaction mixture was cooled using an ice-water bath. The crude solution was directly centrifuged at 8000 rpm for 10 min, and the precipitate was collected and dispersed in toluene. The final quantum dots need to be purified by centrifugation again. Then the obtained quantum dot precursor solution and methyl acetate are mixed at a volume ratio of 1:1.5 (quantum dots: methyl acetate), shaken and centrifuged in a centrifuge at 4000 rpm for ten minutes, the precipitate is dispersed with toluene and stored at 8°C for later use.

[0126] (3) Preparation of perovskite quantum dot film. The precursor solution needs to be purified with methyl acetate. The purification step is to purify the perovskite quantum dot precursor solution to be purified and methyl acetate twice at a volume ratio of 1:1.2. The specific purification step is: mix the perovskite quantum dot solution and methyl acetate at a volume ratio of 1:1.2, shake and centrifuge at 4000 rpm for ten minutes. After centrifugation, pour off the upper clear liquid and disperse the lower solid with toluene.

[0127] Then, a fixed amount of the purified precursor solution (20 μL) was spin-coated onto a quartz glass sheet to obtain a uniform precursor coating. Spin coating parameters: 1000 rpm for 10 s, 2000 rpm for 20 s. The quartz plate with the precursor coating was then placed in a vacuum oven to accelerate the evaporation of toluene under vacuum suction. It was placed in a nitrogen atmosphere for protection and standby.

[0128] (4) The structure of the perovskite quantum dot ammonia gas sensor is the same as that of Example 1.

[0129] Example 3

[0130] (1) First, cut the quartz glass into 1 cm × 1 cm pieces using a glass cutter, wipe the surface stains with an acetone cotton ball, and then place the quartz substrate in isopropanol-acetone-water-acetone-isopropanol ultrasonic treatment for 15 min each, and dry it in a 70°C oven for later use.

[0131] (2) Perovskite quantum dots were synthesized by hot injection. Cs2CO3 (0.814 g) was added to a 100 mL three-necked flask together with octadecene (ODE) (30 mL) and oleic acid (OA) (2.5 mL), dried at 120 °C for 1 h, and then heated to 160 °C under N2 until all Cs2CO3 reacted with OA to obtain cesium oleate solution. The cesium oleate solution was kept at 160 °C before injection to avoid solidification. 24.0 mL ODE, 10 mL OA and PbBr2 (1.38 g) were placed in a 250 mL flask, vacuumed at 120 °C for 30 min and heated to 180 °C under nitrogen flow. 8 mL of cesium oleate solution (0.08 mol in ODE) was quickly injected. Within 5 s, the reaction mixture was cooled using an ice-water bath. The crude solution was directly centrifuged at 8000 rpm for 10 min, and the precipitate was collected and dispersed in toluene. The final quantum dots need to be purified by centrifugation again. Then the obtained quantum dots are mixed with methyl acetate in a volume ratio of 1:1 (quantum dots: methyl acetate), shaken and centrifuged in a centrifuge at 4000 rpm for ten minutes, the precipitate is dispersed with toluene and stored at 8°C for later use.

[0132] (3) Preparation of perovskite quantum dot film. The precursor solution needs to be purified by methyl acetate. The purification step is to purify the perovskite quantum dot precursor solution once with methyl acetate at a volume ratio of 1:1.5. The specific purification step is: mix the perovskite quantum dot solution and methyl acetate at a volume ratio of 1:1.5, shake and centrifuge at 4000 rpm for ten minutes. After centrifugation, pour off the upper clear liquid and disperse the lower solid with toluene.

[0133] Then, a fixed amount of the purified precursor solution (20 μL) was spin-coated onto a quartz glass sheet to obtain a uniform precursor coating. Spin coating parameters: 1000 rpm for 10 s, 2000 rpm for 20 s. The quartz plate with the precursor coating was then placed in a vacuum oven to accelerate the evaporation of toluene under vacuum suction. It was placed in a nitrogen atmosphere for protection and standby.

[0134] (4) The structure of the perovskite quantum dot ammonia gas sensor is the same as that of Example 1.

[0135] Effect Example 1 Response value and ammonia concentration relationship curve

[0136] The perovskite quantum dot ammonia gas sensor prepared in Example 1 was taken, and after the ammonia concentration was calibrated (each calibrated ammonia can be obtained by taking pure ammonia and connecting nitrogen to dilute it according to the required concentration ratio, and its concentration can be calculated according to the dilution ratio), the fluorescence response value of the gas sensor was measured under the condition of 365nm excitation wavelength. The data are shown in the following Table 1, Figure 4 shown.

[0137] Table 1

[0138]

[0139] like Figure 4 As shown in the figure, when the sensor works at room temperature, the response value of the sensor shows a good linear relationship with the ammonia gas concentration between 100ppm and 900ppm. In the 25-50ppm range, the curve regression equation is (F-F0) / F0=0.00219+0.00166[Q](R 2 >0.98), in the 50-350ppm range, the curve regression equation is (F-F0) / F0=0.07197+3.83038×10 -4 [Q](R 2 >0.98), where F is the fluorescence intensity of the gas sensor (perovskite quantum dot film) when it is exposed to ammonia, F0 is the fluorescence intensity of the gas sensor (perovskite quantum dot film) when it is only exposed to background gas (excluding ammonia), and [Q] is the ammonia concentration.

[0140] Effect Example 2 Response value and recovery response curve of ammonia concentration

[0141] The perovskite quantum dot ammonia gas sensor prepared in Example 1 was used to measure the recovery response curve of the gas sensor under different ammonia concentrations and an excitation wavelength of 365 nm. The data are shown in Table 2. Figure 5-8 shown.

[0142] Table 2

[0143]

[0144]

[0145] Note: F is the fluorescence intensity of the gas sensor (perovskite quantum dot film) when it is in contact with ammonia, and F0 is the fluorescence intensity of the gas sensor (perovskite quantum dot film) when it is only in contact with background gas (excluding ammonia);

[0146] Response time refers to the time required for the gas sensor (perovskite quantum dot film) to reach 90% of the stable response value from the time it contacts the measured gas.

[0147] The recovery time refers to the time required for the gas sensor (perovskite quantum dot film) to reach 10% of the stable response value after being separated from the measured gas.

[0148] From Table 2, Figure 5 It can be seen that:

[0149] (1) The response value of the perovskite quantum dot sensor is related to the purification ratio. It is best to keep the same purification ratio when using the sensor.

[0150] (2) When the sensor is operated at room temperature, the sensor can fully recover (recover to more than 90% of the original value) after generating a response at 25-350 ppm, and the response time is approximately between 10-14 s, and the recovery time is approximately between 30-42 s.

[0151] like Figure 6 As shown, when the gas sensor in Example 1 is operated at room temperature 25° C. and the ammonia concentration is 35 ppm, the response time of the gas sensor is about 14 s and the recovery time is about 32 s.

[0152] like Figure 7 As shown, when the gas sensor in Example 2 is operated at room temperature 25° C. and the ammonia concentration is 50 ppm, the response time of the gas sensor is about 10 s and the recovery time is about 42 s.

[0153] like Figure 8As shown, when the gas sensor in Example 3 is operated at room temperature 25° C. and the ammonia concentration is 100 ppm, the response time of the gas sensor is about 10 s and the recovery time is about 34 s.

[0154] Effect Example 3 Selectivity of Ammonia Sensor to Detection Objects

[0155] The perovskite quantum dot ammonia gas sensor prepared in Example 1 was used to detect the contents of other substances under the condition of an excitation wavelength of 365 nm. The detection results are shown in Table 3. Fig. 9 shown.

[0156] Table 3

[0157] Detection object <![CDATA[(Response value (F - F0) / F0)]]> acetone -0.034 <![CDATA[H2O]]> -0.194 Isopropyl alcohol -0.136 HCl -0.107 Ethanol -0.154 <![CDATA[CO2]]> -0.080 Methylamine -0.185 <![CDATA[NH3(100ppm)]]> 1.25

[0158] Note: The detection objects in Table 3 are all volatile substances. In the specific experiments, the fluorescence intensity is detected using the vapor of these specific substances.

[0159] From Table 3, Fig. 9 It can be seen that:

[0160] (1) Except for ammonia, other gases will cause fluorescence quenching, while only ammonia can enhance the fluorescence intensity of perovskite quantum dots. The ammonia sensor prepared using perovskite quantum dots has strong selectivity for ammonia.

[0161] (2) When the gas sensor is operating at room temperature (25°C) and the ammonia concentration is 100 ppm, the gas sensor's response to ammonia is greater than that to other detection gases. The gas sensor exhibits good selectivity.

[0162] Effect Example 4

[0163] (1) Surface changes of perovskite quantum dots after ammonia treatment

[0164] Take the perovskite quantum dot film prepared in step (3) of Example 1, treat it with ammonia gas, and measure the X-ray photoelectron spectrum (XPS spectrum) of the perovskite quantum dots. Figure 10-12 .

[0165] Fig.10 Shown is a schematic diagram of the mode of combination of perovskite quantum dots and ammonia.

[0166] Fig.11 This is the XPS spectrum of perovskite quantum dots before ammonia treatment. Fig.12 This is the XPS spectrum of perovskite quantum dots after ammonia treatment. Fig.11 , 12 It can be seen that in the CsPbBr3 quantum dots before ammonia treatment, only one peak at 401.1eV belongs to -NH3 +, which is caused by the protonation reaction of the amino-containing ligand; for the CsPbBr3 quantum dots treated with ammonia, a new peak can be detected at 399.05eV, which comes from NH3; taking the CsPbBr3 quantum dot film as an example, after deamination, the surface Pb 2+ The interaction between ions decreases, and the new peaks of NH3 and Pb 2+ The binding is a non-covalent bond, making the ammonia passivation of CsPbBr3 quantum dot film a dynamic process.

[0167] From the above, it can be seen that the fluorescence intensity can be significantly enhanced through ammonia-lead coordination passivation without destroying the original structure and optical properties of quantum dots.

[0168] (2) Luminescence properties of perovskite quantum dots after ammonia treatment

[0169] The unpurified perovskite quantum dot precursor solution prepared in step (2) of Example 1 is taken as the unpurified perovskite quantum dots.

[0170] The purified perovskite quantum dot precursor solution prepared in step (3) of Example 1 is taken as the purified perovskite quantum dots.

[0171] Photoluminescence spectrum detection method: Under the condition of 365nm, the time-resolved photoluminescence spectrum (TRPL) of the above quantum dots was detected.

[0172] The specific results can be seen in Tables 4 and 5 below.

[0173] Table 4

[0174] Unpurified perovskite quantum dots τ[ns] <![CDATA[τ1[ns]]]> <![CDATA[A1[%]]]> <![CDATA[τ2[ns]]]> <![CDATA[A2[%]]]> Before ammonia treatment 6.97 3.83 81.22 20.58 18.78 After ammonia treatment 7.68 4.48 87.27 29.65 12.73

[0175] Note: The PL decay in Table 4 is fitted according to the double exponential function. Obtained, where: τ refers to the total fluorescence lifetime, τ1 refers to the radiation lifetime, A1 refers to the proportion of the radiation component lifetime in the total fluorescence lifetime, τ2 refers to the non-radiation lifetime, and A2 refers to the proportion of the non-radiation component lifetime in the total fluorescence lifetime.

[0176] Table 5

[0177]

[0178] Note: The PL decay in Table 5 is fitted according to the three exponential function. Obtained, where: τ refers to the total fluorescence lifetime, τ1 refers to the radiation lifetime, A1 refers to the proportion of the radiation component lifetime in the total fluorescence lifetime, τ2 and τ3 refer to the non-radiative component lifetimes, and A2 and A3 refer to the proportions of different non-radiative component lifetimes in the total fluorescence lifetime.

[0179] According to Table 4 and Table 5, we can know that:

[0180] (1) After purification by methyl acetate, a large number of surface defects appeared in the perovskite quantum dots. Specifically, the fluorescence lifetime of the quantum dots after purification changed from a two-exponential fitting to a three-exponential fitting. When the lifetime increases, it indicates that the non-radiative components are more complex, the luminescence pathways are more, and therefore there are more defects.

[0181] (2) After ammonia treatment, the proportion of non-radiative recombination lifetime in the total fluorescence lifetime is reduced and non-radiative recombination is suppressed. It can be seen that the surface defects of perovskite quantum dots are passivated by ammonia.

[0182] Effect Example 5

[0183] The perovskite quantum dot ammonia gas sensor prepared in Example 1 was used to measure the response value of the gas sensor to 100 ppm ammonia at different operating temperatures under the condition of 365 nm excitation wavelength. The response results are shown in Table 6. Fig.13 shown.

[0184] Table 6

[0185]

[0186]

[0187] From Table 6, Fig.13 It can be seen that when the operating temperature range is -40-70℃, the sensor response value is basically stable. The sensor has a wide operating temperature range and good stability.

[0188] The above contents are only examples within the applicable scope of the present invention and do not represent the applicable scope of the present invention. Therefore, improvements and changes within the scope of the present invention are all within the scope of the present invention.

Claims

1. An ammonia sensor based on perovskite quantum dots, characterized in that: It includes: A gas sensor, used for sensing the concentration of ammonia and converting it into fluorescence intensity, wherein the gas sensor comprises a perovskite quantum dot film, wherein the perovskite quantum dots in the perovskite quantum dot film are perovskite quantum dots with surface defects; the perovskite quantum dots are nano-scale perovskite crystals, and the perovskite quantum dots are CsPbBr3 quantum dots; The synthesis of the perovskite quantum dots is carried out according to the following steps: mixing a compound containing A and a ligand, drying at 110-130° C. for 0.5-1.5 h, and reacting at 60-200° C. under a nitrogen atmosphere to obtain an A-ligand; wherein A in the A-ligand is a cesium ion, and the ligand in the A-ligand is oleic acid or oleylamine; In a solvent, the A-ligand and BX are mixed and reacted. After the reaction is completed, the precursor solution of the perovskite quantum dots is obtained by centrifugation, washing and purification. Wherein, B is a lead ion Pb 2+ , wherein X is a bromide ion Br - , the washing solvent is methyl acetate, and the volume ratio of the precursor solution of the perovskite quantum dots obtained after the centrifugation to the washing solvent is 1: (1-1.5); An excitation light source, used for irradiating the gas-sensitive element to generate a fluorescent signal; The fluorescence receiving element is used to receive the fluorescence signal generated by the gas-sensitive element and record the corresponding fluorescence intensity.

2. The ammonia sensor based on perovskite quantum dots according to claim 1, characterized in that: The compound containing A is Cs2CO3.

3. The ammonia sensor based on perovskite quantum dots according to claim 1, characterized in that: The solvent is octadecene.

4. The ammonia sensor based on perovskite quantum dots according to claim 1, characterized in that: The A-ligand was mixed with the BX at a concentration of 0.01 mol / mL.

5. The ammonia sensor based on perovskite quantum dots according to claim 1, characterized in that: The centrifugal condition is 4000-8000 rpm for 10 min.

6. The ammonia sensor based on perovskite quantum dots according to claim 1, characterized in that: The volume ratio of the precursor solution of the perovskite quantum dots obtained after the centrifugation to the washing solvent is 1:1, 1:1.2 or 1:1.

5.

7. The ammonia sensor based on perovskite quantum dots according to claim 1, characterized in that: The perovskite quantum dot film is attached to the surface of the fluorescence receiving element or the surface of the carrier device.

8. The ammonia sensor based on perovskite quantum dots according to claim 7, characterized in that: The perovskite quantum dot film is prepared according to the following steps: coating the precursor solution of the perovskite quantum dots on the surface of the fluorescent receiving element or the surface of the carrier device.

9. The ammonia sensor based on perovskite quantum dots according to claim 8, characterized in that: The coating method is a spin coating method, a blade coating method, a drop coating method or a slit extrusion coating method.

10. The ammonia sensor based on perovskite quantum dots according to claim 9, characterized in that: In the spin coating method, the spin coating conditions are firstly 1000 rpm for 10 s and then 2000 rpm for 20 s.

11. The ammonia sensor based on perovskite quantum dots according to claim 7 or 8, characterized in that: The object carrier is made of quartz glass or a flexible substrate.

12. The ammonia sensor based on perovskite quantum dots according to claim 11, characterized in that: The flexible substrate is a polyethylene flexible substrate, a PET substrate, a PMMA substrate or paper.

13. The ammonia sensor based on perovskite quantum dots according to claim 7, characterized in that: When the perovskite quantum dot film is attached to the surface of the carrier device to form the gas sensor, the gas sensor is placed between the excitation light source and the fluorescence receiving element; When the perovskite quantum dot film is attached to the surface of the fluorescence receiving element, the fluorescence receiving element can receive the light emitted by the excitation light source.

14. The ammonia sensor based on perovskite quantum dots according to claim 1, characterized in that: The excitation light source is an LED lamp; The fluorescent receiving element is a diode; The gas sensor, the excitation light source and the fluorescence receiving element are placed in a housing; The ammonia sensor also includes a signal analysis system, which is connected to the fluorescence receiving element. The signal analysis system receives the fluorescence signal from the fluorescence receiving element, analyzes it and outputs an electrical signal.

15. The ammonia sensor based on perovskite quantum dots according to claim 14, characterized in that: The diode is a silicon diode.

16. The ammonia sensor based on perovskite quantum dots according to claim 15, characterized in that: The silicon diode has a built-in filter.

17. The ammonia sensor based on perovskite quantum dots according to claim 14, characterized in that: When the gas sensor, the excitation light source and the fluorescence receiving element are placed in a housing, the excitation light source and the fluorescence receiving element are connected to the housing through a fixing device; When the gas sensor, the excitation light source and the fluorescence receiving element are placed in a housing, a socket structure is provided between the excitation light source and the fluorescence receiving element, and the socket structure is fixed on the housing; the socket structure is used to place the gas sensor; The shell is a black hollow structure; The shell is provided with an air inlet and an air outlet.

18. The ammonia sensor based on perovskite quantum dots according to claim 17, characterized in that: The fixing device is a screw.

19. A method for quantitative detection of ammonia, characterized in that: It includes the following steps: (1) Under the irradiation of excitation light, a standard curve of ammonia concentration-fluorescence intensity is constructed using a gas sensor (F-F0) / F0-[Q], wherein: F is the fluorescence intensity of the gas sensor when it contacts ammonia, F0 is the fluorescence intensity of the gas sensor before contacting ammonia, and [Q] is the ammonia concentration; The gas-sensitive element is a gas-sensitive element as described in any one of claims 1 to 18; (2) Under the irradiation of excitation light, the fluorescence intensity of the gas sensor before contacting the gas to be measured is detected, which is recorded as F0', and the fluorescence intensity of the gas sensor after contacting the gas to be measured is detected, which is recorded as F'; The concentration of ammonia in the gas to be tested can be calculated according to the standard curve in step (1).

20. The method for quantitative detection of ammonia as claimed in claim 19, characterized in that: When the ammonia concentration in step (1) is 25-50 ppm, the standard curve is (F-F0 / F0)=0.00219+ 0.00166 [Q](R 2 >0.98); When the ammonia concentration in step (1) is 50-350 ppm, the standard curve is (F-F0) / F0=0.07197+3.83038×10 -4 [Q](R 2 >0.98).

21. The method for quantitative detection of ammonia as claimed in claim 19, characterized in that: The quantitative detection of ammonia is carried out in the ammonia sensor based on perovskite quantum dots as described in any one of claims 1 to 18.

22. An application of perovskite quantum dots as gas sensors in ammonia detection, wherein: The perovskite quantum dots are the perovskite quantum dots according to any one of claims 1 to 18.

23. A perovskite quantum dot, characterized in that: The surface of the perovskite quantum dot includes a passivation layer, and the passivation layer is a structure formed by passivating the surface defects of the perovskite quantum dot with ammonia; The perovskite quantum dots are the perovskite quantum dots according to any one of claims 1 to 18.

Citation Information

Patent Citations

  • Ammonia gas sensor based on perovskite quantum dots

    CN212228739U